Imported malaria in Changsha municipality - prevalence characteristics and retransmission risk, 2010 - 2019 - Guo-qun LI; Yu LIAO; Meng-xiang CHEN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze prevalence characteristics and the risk of local retransmission of imported malaria from 2010 to 2019 in Changsha municipality, Hunan province and to provide evidences for developing strategies and measures on malaria control.MethodsWe extracted the data on imported malaria cases registered in Changsha municipality from 2010 through 2019; regional information of the same period on demographics, capabilities of disease prevention and control and vector Anopheles mosquitoes surveillance were also collected simultaneously. Descriptive epidemiological methods and adjusted input retransmission risk assessment method were used to analyze prevalence characteristics and the risk of local retransmission of imported malaria.ResultsTotally 402 imported malaria cases were registered in the region during the 10-year period; of the reported cases, 58.0% (233) and 25.4% (102) were falciparum and vivax malaria. Most of the imported malaria cases were males and the majority of the cases were aged 18 to 44 years and migrant workers. More imported malaria cases were reported in Liuyang prefecture. The reported cases were mainly from African countries. The transmission risk index ranged from 73.59 to 21.03 for the 9 prefectures/districts/counties of the municipality, with the highest index for a prefecture and the lowest for a district, the indexes between 60.08 and 52.56 for the three and between 45.06 and 30.04 for the four counties/districts, respectively. ConclusionFor Changsha municipality during 2010 - 2019, the imported malaria cases were mainly falciparum malaria and from Africa countries; the risk of malaria local retransmission is relatively high in a prefecture of the municipality.